Proceedings of the 2016 International Conference on Sensor Network and Computer Engineering 2016
DOI: 10.2991/icsnce-16.2016.8
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Filtering Algorithm Based on Double Clustering and User Trust

Abstract: Abstract.A collaborative filtering algorithm based on double clustering and user trust to solve data sparse and cold start problem is present. This algorithm uses user-clustering matrix to measure the user's degree of similarity, which could reduce the dimension of the user-item matrix. On the other hand it uses user level trust to perform predictions in rating predicting step. The experiments results show that this method could relieve the sparsity problem and improve the accuracy of the prediction results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The author in this [12] incorporated social trust of users into the recommender system and developed a belief system between them. A CFL technique based on dual clustering and user belief was proposed to handle data sparsity and cold start problems [13]. The authors suggested a strategy based on different alternative viewpoints of reliability metrics in this paper [14] to increase the data sparsity issue.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The author in this [12] incorporated social trust of users into the recommender system and developed a belief system between them. A CFL technique based on dual clustering and user belief was proposed to handle data sparsity and cold start problems [13]. The authors suggested a strategy based on different alternative viewpoints of reliability metrics in this paper [14] to increase the data sparsity issue.…”
Section: Related Workmentioning
confidence: 99%
“…The neighbor set is then built based on the user similarity measures by picking the first L users who are closest to user u. We may also calculate the prediction value using the following Eq (13):…”
Section: Simðu; Vþmentioning
confidence: 99%
See 1 more Smart Citation
“…And, due to the open nature of collaborative recommender systems, recommender systems cannot effectively prevent malicious users from injecting fake profile data into the ratings database; Zhang F introduced the social trust of the users into the recommender system and built the trust between them [14]. In order to solve data sparse and cold start problem, Tonglong Tang presented a collaborative filtering algorithm based on double clustering and user trust, which used user-clustering matrix to measure the user's degree of similarity [15]. And, Sajad Ahmadian proposed a method which is based on three different views of reliability measures to improve the data sparse and cold start problem [16].…”
Section: Related Workmentioning
confidence: 99%
“…There must have suitable applications running in cloud platform so that the cloud computing can exert into full play [45]. But how to compile parallel program which can run in cloud platform is very particular.…”
Section: Introductionmentioning
confidence: 99%